Pengaruh Persentase Penduduk Miskin Dan Tingkat Partisipasi Angkatan Kerja Terhadap Indeks Pembangunan Manusia Di Provinsi Bali - Helen, Princes; Afdal Samsuddin, M. (Shofanah Media Berkah, 2025)
This study aims to examine the relationship between PPM (percentage of population living in poverty) and TPAK (percentage of population actively seeking employment) and HDI (Human Development Index) in Bali Province. The quantitative method of this work is based on a multiple linear regression model that analyzes secondary time series data from the Central Bureau of Statistics (BPS) from 1995 to 2024. The PPM variable significantly affects HDI, in contrast to the LPR variable which is not significant. Nonetheless, HDI does benefit from the combination of both. The adjusted R-squared value of 67.3% indicates that PPM and LPR adequately explain the variance in HDI. These findings are useful for the city governments of Bali Province as they highlight areas for improvement in terms of human capital quality and poverty reduction, two important components of sustainable development. Translated with DeepL.com (free version).